Anti-idiotype isolation of a broad and potent influenza A virus-neutralizing human antibody - Olia, Adam S.; Prabhakaran, Madhu; Harris, Darcy R.; Cheung, Crystal Sao-Fong; Gillespie, Rebecca A.; Gorman, Jason; Hoover, Abigayle; Morano, Nicholas C.; Ourahmane, Amine; Srikanth, Abhinaya; Wang, Shuishu; Wu, Weiwei; et al. (Frontiers in Immunology, 2024)
The VH6-1 class of antibodies includes some of the broadest and most potent antibodies that neutralize influenza A virus. Here, we elicit and isolate anti-idiotype antibodies against germline versions of VH6-1 antibodies, use these to sort human leukocytes, and isolate a new VH6-1-class member, antibody L5A7, which potently neutralizes diverse group 1 and group 2 influenza A strains. While its heavy chain derived from the canonical VH6-1 heavy chain gene used by the class, L5A7 utilized a light chain gene, VK1-9, which had not been previously observed in other VH6-1-class antibodies. The cryo-EM structure of L5A7 in complex with Indonesia 2005 hemagglutinin revealed a nearly identical binding mode to other VH6-1-class members. The structure of L5A7 bound to the isolating anti-idiotype antibody, 28H6E11, revealed a shared surface for binding anti-idiotype and hemagglutinin that included two critical L5A7 regions: an FG motif in the third heavy chaincomplementary determining region (CDR H3) and the CDR L1 loop. Surprisingly, the chemistries of L5A7 interactions with hemagglutinin and with anti-idiotype were substantially different. Overall, we demonstrate anti-idiotype-based isolation of a broad and potent influenza A virus-neutralizing antibody, revealing that anti-idiotypic selection of antibodies can involve features other than chemical mimicry of the target antigen.